Control of malt roasting operations for consistent delivery of desired product flavour - Parr, Hebe (2022)
Roasted malts are used in the brewing industry to impart colour and flavour to beers. The diversity of colours and flavours roasted products can provide are dependent upon a variety of factors: roasting time and temperature, initial moisture content, roasting substrate type (i.e. green malt, pale malt, or unmalted barley), and roasting sequence (i.e. stewing, kilning, and/or roasting). The aim of this research was to improve understanding of thermal flavour generation in roasted malt and barley, and thereby improve understanding of roasting process control. In this research, instrumental analysis was employed to positively identify and quantify thermally generated volatile compounds in roasted products, while sensory analysis evaluated the odour activity of identified volatiles, and quantitatively described aroma qualities of roasted products.